Faktor-Faktor Yang Berkaitan Dengan Penglibatan Pengusaha-Pengusaha Projek Ekonomi Di Kawasan Ketengah Dalam Membuat Keputusan - Ismail, Omar (1994)
The main objective of the study was to investigate factors associated with involvement of respondents in making decisions related to agricultural activities. Specifically, the study was aimed to determine the level of involvement of local entrepreneurs in deciding agriculture-based activities initiated by KETENGAH. Selected demografic, communication, attitudes and personality factors were used as independent variables. Forty-five agriculture-related entrepreneurs from the traditional villages in KETENGAH who have undergone specific motivational courses were selected as respondents. A structured interview was administered with each respondent. Data were than analyzed using the " Statistical Package for Social Science" version 4.0. The study revealed that respondents made about 50 percent of the decisions related to their agricultural activities. The level of attitudes towards renewal and their characteristic toward achievement-orientation were found to be moderate. In addition, there was a significant relationship between family income and level of involvement in decision making. A significant difference was also observed between respondents' involvement in decision making and respondents' educational background and attendence in specific motivational courses organised by KETENGAH. Family income, exposure to relevant knowledge, attitudes towards extension work, attitudes towards KETENGAH extension officers, efficacy in public affairs, optimism, achievement-oriented personalities and orientation towards planning have positive